Simultaneous transcriptome and proteome analysis of EA.hy926 cells under stress conditions induced by nanomaterials. Issue 4 (10th September 2018) - Komorowski, Piotr; Siatkowska, Małgorzata; Wasiak, Tomasz; Działoszyńska, Katarzyna; Kotarba, Sylwia; Kądzioła, Kinga; Bartoszek, Nina; Sokołowska, Paulina; Elgalal, Marcin; Sobol‐Pacyniak, Anna; Makowski, Krzysztof; Walkowiak, Bogdan
Abstract: Today, the extensive and constantly growing number of applications in the field of nanotechnology poses a lot of questions about the potential toxicity of nanomaterials (NMs) toward cells of different origins. In our work we employed the tools of molecular biology to evaluate changes that occur in human endothelial cells at the transcriptomic and proteomic level, following 24 h of exposure to three different classes of NMs. Using microarray technology, we demonstrated that 24 h of exposure to silver nanoparticles (SNPs), multiwalled carbon nanotubes (MWCNTs) and polyamidoamine dendrimers (PAMAMs) leads to changes in 299, 1271, and 431 genes, respectively, influencing specific molecular pathways. The 2D‐DIGE and mass spectrometry analysis revealed that differentially expressed proteins were involved in numerous cellular processes, for example, cytoskeletal reorganization, cell growth and proliferation, or response to stress. Both, transcriptome and proteome alterations indicate reorganization of mechanism regulating cell functioning. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1024–1034, 2019.